Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1159/000328390
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Retrograde Flexible Ureteroscopy after Cohen Cross-Trigonal Ureteral Reimplantation

Abstract: Purpose: Retrograde ureteral access after cross-trigonal ureteral reimplantation can be challenging. We present our experience with retrograde ureteral catheterization and flexible ureteroscopy after Cohen cross-trigonal reimplantation in patients presenting with ureteral stones. Materials and Methods: Cystoscopy is performed and a Tiemann ureteral catheter is inserted into the involved ureteral orifice. A retrograde ureterography is performed and hydrophilic guide wire is passed up to the kidney. A dual-lumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Retrogradely Inserted guide wire under cystoscopic guidance with curved tip vascular access catheter and angletipped glide wire De Castro 9 Retrograde 13 Supra-pubic retrograde ureteral catheterization under cystoscopic guidance Lusuardi 10 Retrograde 8 Retrogradely inserted Tiemann ureteral catheter under cystoscopic guidance. And then fURS is passed to the stone Khalil 11 Retrograde 1 Retrogradely inserted curved guide wire into the ureteral orifice and then inserted fURS Adam 3 Retrograde 1 Supra-pubic puncture was done and guide wire was inserted under cystoscope with grasping forceps Emiliani 12 Retrograde 3 7-Fr angled orifice catheter and angled stiff wire is used for first access.…”
Section: Resultsmentioning
confidence: 99%
“…Retrogradely Inserted guide wire under cystoscopic guidance with curved tip vascular access catheter and angletipped glide wire De Castro 9 Retrograde 13 Supra-pubic retrograde ureteral catheterization under cystoscopic guidance Lusuardi 10 Retrograde 8 Retrogradely inserted Tiemann ureteral catheter under cystoscopic guidance. And then fURS is passed to the stone Khalil 11 Retrograde 1 Retrogradely inserted curved guide wire into the ureteral orifice and then inserted fURS Adam 3 Retrograde 1 Supra-pubic puncture was done and guide wire was inserted under cystoscope with grasping forceps Emiliani 12 Retrograde 3 7-Fr angled orifice catheter and angled stiff wire is used for first access.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports on endoscopic lithotripsy for urinary stones after Cohen reimplantation, Inoue et al 3 performed antegrade URS without preoperative placement of ureteral stent. Lusardi et al 4 performed URS without preoperative ureteral stent placement or use of UAS. Emiliani et al 5 performed URS without preoperative ureteral stent placement; however, by inserting a 10/ 12Fr UAS.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic medline database review found only exceptional descriptions of surgical techniques of retrograde catheterization of the Cohen [1, 3]. To our knowledge, we describe the fourth retrograde ureteral access technique.…”
Section: Discussionmentioning
confidence: 99%
“…The retrograde access through Cohen's reimplantation for the minimally invasive treatment of an intradiverticular symptomatic kidney stone combines two major anatomical difficulties [1, 2]. Our technique allows resolving this anatomical problem by the use of a flexible ureterorenoscope coupled with the Holmium-YAG laser.…”
Section: Introductionmentioning
confidence: 99%